2004
DOI: 10.1016/j.ydbio.2004.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling is required for commitment but not initial induction of slow muscle precursors

Abstract: In zebrafish, skeletal muscle precursors can adopt at least three distinct fates: fast, non-pioneer slow, or pioneer slow muscle fibers. Slow muscle fibers develop from adaxial cells and depend on Hedgehog signaling. We analyzed when precursors become committed to their fates and the step(s) along their differentiation pathway affected by Hedgehog. Unexpectedly, we find that embryos deficient in Hedgehog signaling still contain postmitotic adaxial cells that differentiate into fast muscle fibers instead of slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 67 publications
7
83
0
Order By: Relevance
“…Moreover, it also suggests that specification of adaxial cells does not require Hh signaling. These data are consistent with previous findings by Hirsinger and colleagues who showed that Hh signal is required for commitment but not initial induction of slow muscle precursors in zebrafish embryos (Hirsinger et al, 2004). Adaxial cells could form in the yot mutant, however, without Hh signaling, adaxial cells fail to differentiate into slow muscles, instead they differentiate into fast muscles.…”
Section: Regulation Of Smyd1 Expression and Adaxial Cell Formation Bysupporting
confidence: 93%
“…Moreover, it also suggests that specification of adaxial cells does not require Hh signaling. These data are consistent with previous findings by Hirsinger and colleagues who showed that Hh signal is required for commitment but not initial induction of slow muscle precursors in zebrafish embryos (Hirsinger et al, 2004). Adaxial cells could form in the yot mutant, however, without Hh signaling, adaxial cells fail to differentiate into slow muscles, instead they differentiate into fast muscles.…”
Section: Regulation Of Smyd1 Expression and Adaxial Cell Formation Bysupporting
confidence: 93%
“…A similar model has been proposed to explain how fast and slow muscle precursors acquire their different fates (Hirsinger et al, 2004). These authors reported that the fast and slow muscle progenitor pools derive from separate yet overlapping regions of the 6 hpf embryo (similar to the progenitor pools contributing to individual pancreatic buds).…”
Section: Dorsoventral Asymmetry Of the Pancreas Fate Mapmentioning
confidence: 69%
“…To block the development of SMCs, wild-type embryos were incubated either in 0.1 mM cyclopamine (Calbiochem, EMD Chemical, Inc., Gibbstown, NJ, USA; Barresi et al, 2000;Hirsinger et al, 2004) dissolved in 1% DMSO or in 0.15 mM forskolin (Calbiochem; Barresi et al, 2000) dissolved in 2% DMSO in 30% Danieau's solution, from ~5.5 hpf to ~24 hpf. As a control, some embryos were incubated in 2% DMSO in 30 % Danieau's solution alone.…”
Section: Inhibition Of Slow Muscle Development Using a Pharmacologicamentioning
confidence: 99%